Optimal design of pressure vessels including the effect of environment - Pochtman, Yuriy M.; Fridman, Mark M. (Computer Assisted Methods in Engineering and Science; Vol 2 No 1 (1995), 2023)
The paper presents the optimization of thin-walled structures such as vertical cylindrical reservoirs subject to pitting corrosion. The function of the structure utility is taken as an optimization criterion. The choice of an optimal thickness distribution of the reservoir shell along its height is determined from the conditions of its uniform reliability.